Reability Analysis and Scedulling Preventive Maintenance for Spray Dryer Machine - Nushron Ali Mukhtar (Universitas Trunojoyo Madura, 2022)
The activity of implementing proper machine maintenance is a must in a company. PT Arwana Citramulia Tbk is a company that produces ceramic tiles. The machine used is a spray dryer machine. The company aims to determine whether there is a schedule or time interval for machine maintenance. The method used is (RCM) Reliability Centered Maintenance. RCM is a process for determining the actions that must be taken so that the system is in good condition. Components are reviewed from FMEA (Failure Mode and Effect Analysis). The risk assessment is obtained from calculating the RPN (Risk Priority Number), then determining the distribution of each component. Calculation of MTTR and MTBF values, and finally determines the maintenance time interval. From the FMEA results, three risk priority components were obtained, namely the nozzle, piston pump, and vibration filter slip tank. Maintenance intervals on the nozzle component with a maintenance interval of 694 hours , piston pump with a maintenance interval of 758 hours, vibration filter slip tank with a maintenance interval of 292 hours per year. The results of this study indicate that there are three components that have a high failure rate and must receive scheduled maintenance to reduce the failure of the spray diyer machine